Cdx2 Animal Models Reveal Developmental Origins of Cancers - Chawengsaksophak, Kallayanee (Genes, 2019)
The Cdx2 homeobox gene is important in assigning positional identity during the finely orchestrated process of embryogenesis. In adults, regenerative responses to tissues damage can require a replay of these same developmental pathways. Errors in reassigning positional identity during regeneration can cause metaplasias-normal tissue arising in an abnormal location-and this in turn, is a well-recognized cancer risk factor. In animal models, a gain of Cdx2 function can elicit a posterior shift in tissue identity, modeling intestinal-type metaplasias of the esophagus (Barrett's esophagus) and stomach. Conversely, loss of Cdx2 function can elicit an anterior shift in tissue identity, inducing serrated-type lesions expressing gastric markers in the colon. These metaplasias are major risk factors for the later development of esophageal, stomach and colon cancer. Leukemia, another cancer in which Cdx2 is ectopically expressed, may have mechanistic parallels with epithelial cancers in terms of stress-induced reprogramming. This review will address how animal models have refined our understanding of the role of Cdx2 in these common human cancers.
Keywords: nádory žaludku; Esophagus; metaplazie; kolon; regulace genové exprese u nádorů; Humans; nádory tračníku; Disease Progression; Metaplasia; metaplasia; Stomach; Colonic Neoplasms; nádory jícnu; homeoboxové geny; Genes, Homeobox; cancer; Colon; lidé; zvířata; Esophageal Neoplasms; CDX2 Transcription Factor; žaludek; ezofágus; animal models; progrese nemoci; Animals; transkripční faktor CDX2; Gene Expression Regulation, Neoplastic; Disease Models, Animal; Cdx; Stomach Neoplasms; modely nemocí na zvířatech